Macrophage Migration Inhibitory Factor (MIF) Prevents Maternal Death, but Contributes to Poor Fetal Outcome During Congenital Toxoplasmosis - Gomes, Angelica O.; Barbosa, Bellisa F.; Franco, Priscila S.; Ribeiro, Mayara; Silva, Rafaela J.; Gois, Paula S. G.; Almeida, Karine C.; Angeloni, Mariana B.; Castro, Andressa S.; Guirelli, Pâmela M.; Cândido, João V.; Chica, Javier E. L.; et al. (Frontiers in Microbiology, 2018)
MIF is a pro-inflammatory cytokine that plays important roles in physiology, pathology, immunology and parasitology, including the control of infection by protozoa parasites such as Toxoplasma gondii. As the MIF function in congenital toxoplasmosis is not fully elucidated yet, the present study brings new insights for T. gondii infection in the absence of MIF based on pregnant C57BL/6MIF-/- mouse models. Pregnant C57BL/6MIF-/- and C57BL/6WT mice were infected with 05 cysts of T. gondii (ME49 strain) on the first day of pregnancy (dop) and were euthanized at 8 dop. Non-pregnant and non-infected females were used as control. Our results demonstrated that MIF-/- mice have more accentuated change in body weight and succumbed to infection first than their WT counterparts. Otherwise, pregnancy outcome was less destructive in MIF-/- mice compared to WT ones, and the former had an increase in the mast cell recruitment and IDO expression and consequently presented less inflammatory cytokine production. Also, MIF receptor (CD74) was upregulated in MIF-/- mice, indicating that a compensatory mechanism may be required in this model of study. The global absence of MIF was associated with attenuation of pathology in congenital toxoplasmosis, but resulted in female death probably because of uncontrolled infection. Altogether, ours results demonstrated that part of the immune response that protects a pregnant female from T. gondii infection, favors fetal damage.